Hydrogel-based drug delivery systems for cancer therapy - Mishra B.; Singh J. (My University, 2025)
Hydrogels have been employed for applications like wounds, burns, dressings, contact lenses, tissue engineering applications, to name a few. The potential of hydrogel application for localized cancer therapy has also been widely explored. This chapter aims to provide an insight into the injectable hydrogel systems for local application to the tumor site. The chapter discusses the basics of hydrogel and its classification. The hydrogels are classified according to their triggering stimuli like pH, temperature, magnet, light, and ultrasound are discussed in detail. The basic design and mechanism of action of several stimuli-responsive hydrogels with few researched examples are discussed. In the end, an overview of the marketed and patented hydrogels for cancer therapy has been provided. © 2021 Elsevier Inc. All rights reserved.